Quota Nonadoption in Japan: The Role of the Women's Movement and the Opposition. Issue 1 (17th March 2015) - Gaunder, Alisa
Abstract : In 2003, Japan's dominant Liberal Democratic Party (LDP) committed to the goal of 30% female representation in management and political positions by 2020 to conform with the international norm to promote women's leadership. This nonbinding commitment received widespread media attention. In 2012, Prime Minister Shinzō Abe reemphasized this goal before the lower house election. Yet, in his first cabinet, Abe appointed only two women. Moreover, in the 2013 upper house election, the LDP fielded only 9 women out of 79 candidates, nowhere near the 30% candidate goal (Torres 2013). In September 2014, Abe appointed five new women in his cabinet reshuffle, two of whom were forced to resign a month later due to scandals. Four women currently sit on the cabinet due to one female replacement (Flackler 2014). Despite Abe's attempts to increase women in his cabinet, most agree that Japan is not on target to meet the 30% benchmark (Gender Equality Bureau 2012).